2018
DOI: 10.1016/j.heares.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with social sounds alters c-Fos expression in auditory cortex and interacts with estradiol in locus coeruleus

Abstract: When a social sound category initially gains behavioral significance to an animal, plasticity events presumably enhance the ability to recognize that sound category in the future. In the context of learning natural social stimuli, neuromodulators such as norepinephrine and estrogen have been associated with experience-dependent plasticity and processing of newly salient social cues, yet continued plasticity once stimuli are familiar could disrupt the stability of sensorineural representations. Here we employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 79 publications
(104 reference statements)
0
21
0
Order By: Relevance
“…Thus, it is conceivable that inhibitory control deficits might be the neural basis for increases in novel exploration and subsequently for the improvement in unconstrained flexibility. Moreover, as gregarious animals, mice normally live in groups and are adapted to supporting and interacting with conspecific individuals [13, 46, 47]. However, isolation rearing would interrupt these relationships and individual mice would be forced to navigate their the complex surroundings and survival problems alone, which may increase investigation motivation to compensate for the absence of social support [12, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is conceivable that inhibitory control deficits might be the neural basis for increases in novel exploration and subsequently for the improvement in unconstrained flexibility. Moreover, as gregarious animals, mice normally live in groups and are adapted to supporting and interacting with conspecific individuals [13, 46, 47]. However, isolation rearing would interrupt these relationships and individual mice would be forced to navigate their the complex surroundings and survival problems alone, which may increase investigation motivation to compensate for the absence of social support [12, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple centralized neuromodulatory systems widely innervate sensory and integrative brain regions, and respond to changes in environmental conditions [ 64 ]. For example, noradrenergic neurons within the locus coeruleus are sensitive to behaviorally important information, such as social context or stress, are affected by social experience, influence connectivity in neural networks related to salience and affect, and alter performance on sensory and cognitive tasks [ 201 , 202 , 203 , 204 , 205 , 206 ]. These kinds of similarities in some of the aspects of how serotonergic, noradrenergic, and other neurochemical systems work have led to the view that these systems may cooperate in regulating integrative neural functions [ 74 , 207 ].…”
Section: Do Hearing Loss and Social Isolation Physiologically Convmentioning
confidence: 99%
“…Importantly, it has recently been shown that oxytocin release during repetitive exposure to pup vocalizations induced long term cortical changes in non-maternal mice, such that cortical responses to calls were highly temporally precise, similar to the maternal brain (Marlin et al 2015). Finally, there is evidence that pup vocalizations activate the locus coeruleus, a subcortical nucleus synthesizing norepinephrine, in virgin and maternal mice (Moreno et al 2018). This demonstrates that vocalizations may themselves be able to activate neuromodulatory centers for the induction of plasticity, possibly increasing a dam's sensitivity to high-probability features defining stimulus category in the absence of external factors (Moreno et al 2018).…”
Section: Neural Correlates Of Plasticity In the Rodent Auditory Cortexmentioning
confidence: 99%
“…Finally, there is evidence that pup vocalizations activate the locus coeruleus, a subcortical nucleus synthesizing norepinephrine, in virgin and maternal mice (Moreno et al 2018). This demonstrates that vocalizations may themselves be able to activate neuromodulatory centers for the induction of plasticity, possibly increasing a dam's sensitivity to high-probability features defining stimulus category in the absence of external factors (Moreno et al 2018).…”
Section: Neural Correlates Of Plasticity In the Rodent Auditory Cortexmentioning
confidence: 99%